2022
DOI: 10.3390/biomedicines10092077
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Specific Laminin Alpha 4 Deletion Preserves Adipose Tissue Health despite Increasing Adiposity

Abstract: Laminins are heterotrimeric glycoproteins with structural and functional roles in basement membranes. The predominant laminin alpha chain found in adipocyte basement membranes is laminin α4 (LAMA4). Global LAMA4 deletion in mice leads to reduced adiposity and increased energy expenditure, but also results in vascular defects that complicate the interpretation of metabolic data. Here, we describe the generation and initial phenotypic analysis of an adipocyte-specific LAMA4 knockout mouse (Lama4AKO). We first pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
1
1
1
Order By: Relevance
“…Several studies have shown that LAMA4 knock-out in mice resulted in healthier phenotypes and metabolisms [13,18,20]. Contrasting these results, we did not find associations of low LAMA4 expression with metabolically healthy obesity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that LAMA4 knock-out in mice resulted in healthier phenotypes and metabolisms [13,18,20]. Contrasting these results, we did not find associations of low LAMA4 expression with metabolically healthy obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…We were unable to confirm this finding in our cohort (Figure 1D), possibly due to our cohort's structure comprising of individuals predominantly with obesity and a low number of individuals with normal or overweight. Nevertheless, our findings support previous reports [18,20,21] which associated LAMA4 expression with obesity and increased fat mass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation